Contemporary Outdoor Sculpture at The Guild : An Exhibition To Commemorate the Fiftieth Anniversary of The Guild 1932-1982 - Etrog, Sorel (Scarborough : The Guild, 1982)
Andre, Carl ; Barkley, Alan ; Bentham, Douglas ; Bieler, Ted ; Bowers, Robert ; Broere, John ; Fauteux, Andre ; Johnston, Peter ; Murray, Robert ; Schwarz, Judith ; Therrien, Denise ; etc.
Contemporary Outdoor Sculpture at The Guild : An Exhibition To Commemorate the Fiftieth Anniversary of The Guild 1932-1982, The Guild, Scarborough, August 3 - October 14, 1982
English
kunstcatalogus